Dose-Dependent Genotoxic and Cytotoxic Activity of Auramine in Mice: A Preliminary Study - Roy, Sumitava; Mukherjee, Raktim; Biswas, Surjyo Jyoti; Karmakar, Susanta Roy (Asian Journal of Biological and Life Sciences)
The present study was conducted to find out the deleterious effects of Auramine by studying cytogenetical parameters, namely chromosome aberration (CA), mitotic indices (MI) and sperm head anomaly (SHA) in mice. Two different doses (10% and 15% of LD50) of Auramine were fed to different groups of mice to find out whether there is any appreciable difference in toxicity. Experiments were carried out at three different fixation intervals, namely, 7D, 14D and 21D, maintaining suitable controls. The investigation reveals that feeding of dye induced geno-toxicity and cyto-toxicity. These produced greater amount of CA, SHA along with a general increase in the MI in both Auramine10% and Auramine15% fed series with some degree of variations. Thus, the increased level of genotoxicity and cytotoxicity could be attributed to chronic feeding of the chemical. Although our present experiment was an initial attempt to test the toxic effects of Auramine in two different doses, hopefully it will open up new vistas to solve the critical issues yet to be discovered.
Keywords: Auramine; cytotoxicity; Genotoxicity; Mice